The effect of food on the pharmacokinetics of WXFL10203614, a potential selective JAK1 inhibitor, in healthy Chinese subjects - Huang, Kai; Shi, Yunfei; Chu, Nannan; Que, Linling; Ding, Ying; Qian, Zhenzhong; Qin, Wei; Gu, Xianghong; Wang, Jiakun; Zhang, Zhiwei; Xu, Jianguo; He, Qing (Frontiers in Pharmacology, 2022)
Abstract Objective: This study was performed to investigate the effect of food on the pharmacokinetics (PK) of WXFL10203614 in healthy Chinese subjects. Methods: This was a randomized, open-label, single-dose, two-treatment (fed vs. fasted), two-period, two-sequence, crossover study. 14 eligible subjects were averagely randomized into 2 sequences and then received 10 mg WXFL10203614 under fasted or fed condition. In each period, the blood samples were collected from 0 h (pre-dose) and serially up to 72 h post-dose, and plasma concentrations were detected using the high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) method. The effect of food on the PK profile and safety of WXFL10203614 were assessed. Results: 70 subjects were screened, and 14 subjects (10 male and 4 female) were enrolled and completed the study. Under the fasted condition, WXFL10203614 was absorbed rapidly with a Tmax of 0.98 h. The absorption rate was slower, Tmax delayed by 2.98 h, and the Cmax decreased by 16.3 % when WXFL10203614 administered after the high-fat and high-calorie diet, other PK parameters were not affected. The 90 % confidence intervals (CIs) for the ratio (fed/fasted) of geometric means of the Cmax, AUC0-t and AUC0-∞ were 0.73-1.01, 0.90-1.03 and 0.90-1.03, indicating that the high-fat and high-calorie diet might impact the absorption process of WXFL10203614. Although the Cmax was slightly decreased, there was no significant difference in the Cmax under fasted and fed conditions. Thus, it was not considered clinically significant owing to the small magnitude of changes in Cmax. All Treatment-emergent adverse events (TEAEs) were mild and resolved spontaneously without treatment. Conclusion: Food had no clinically relevant effects on drug system exposure of WXFL10203614. It was well tolerated under fasted and fed conditions in healthy Chinese subjects, so WXFL10203614 could be administered orally with or without food. Clinical trials registration number: http://www.chinadrugtrials.org.cn/index.html # CTR20191636